Síntese e caracterização da metilcelulose produzida a partir do caroço de manga para aplicação como aditivo em argamassas - Cruz, Sebastião Francelino da (2011)
The mango is one of the most popular fruits in Brazil, and the best know type is Mangifera indica L. The production of this fruit is seasonal and its industrialization has grown in the last years as a means of diminishing loss in the harvest time. The mango processing generates a great amount of residues, around 40 to 60% of the entire amount of raw material. From the residues generated, 12 to 15% is made up of peel and 15 to 20% is seeds. The residues cannot be accumulated indefinitely where they were produced, and are normally discarded with no previous treatment, far from the processing unit. In this sense, the use of the mango seed as a source of cellulose is an alternative in order to diminish the loss and impact on the environment. In this study, the mango seed of the Ubá variety of mangifera indica L. was used as a source of cellulose. The mango seed, originating from a juice factory in the municipality of Araguari-MG, showed a content of cellulose of 55.00% ± 1.0, while the content of Klason lignin was 23.85% ± 0.3. The fibres of the mango seed were used in the production of methylcellulose and the samples were produced by means of heterogeneous methylation using dimethyl sulfate (DMS) and iodomethane as alkylating agents. The methylcelluloses produced were characterized as to their thermal properties by means of scanning exploratory calorimetry (DSC) and thermogravimetric analysis (TGA). The crystalline fraction of the polymers was determined by diffraction of X-rays (DRX), and the substitution degrees (GS) were determined by chemical means. The GS values, determined by chemical means were of 1.35 for MCD and 0.45 for MCI, showing a higher substitution in the synthesis using DMS as methylation agent. Aqueous solutions of methylcellulose, in the concentration of 0.2% m/m and 0.6% m/m (polymer mass/cement mass) were used as an additive in mortar and its effect was assessed, when newly prepared, by means of Consistency Index (CI) tests, density and water retention. After hardened, tests by means of the assessment of potential resistance in adherence and traction (Ra) were carried out. The methylcellulose samples obtained with DMS (MCD) and iodomethane (MCI) as methylate agents, used in the proportion of 0.6% w/w, showed better result; the increase was of 27.75% and 71.54% in the IC and an increase of 23.33% and 26.67% respectively in the Ra, showing that polymers can be used in the production of adhesive mortars.